United Nations Involvement in Kashmir Conflict - Wani, Hilal Ahmad; Suwirta, Andi (SUSURGALUR, 2014)
ABSTRACT: Third party involvement or mediation is one of the methods to resolve the conflict. Mediation is the process of conflict resolution. In Kashmir conflict, the major involvement for the conflict resolution is the role of United Nations (UN). Actually, Kashmiris have been suppressed through the process of centralization and over centralization. Anyway, United Nations resolutions strengthened the Kashmiri movement of freedom. However, it is also reality that, somehow and somewhere, UN had failed in Kashmir conflict in order to give the final touch to its resolutions. In addition, Kashmir conflict remains a longstanding dispute in international politics. The Kashmir imbroglio could have been resolved if UN had taken its responsibility. On the other side, the main failure of third party mediation in Kashmir context is Indiaâs strong rejection to third party mediation. It is not wrong that if Kashmiris were demanding their due share and due rights that is right of self-determination and freedom. All parties of the Kashmir conflict should respect the covenants and resolutions of UN and protect human blood, which is costless. Finally, it can be said that India cannot win the hearts of Kashmiris through might and force basis, rather it is only possible through tolerance, love, respect the dignity of Kashmiris, and above all through greater autonomy. KEY WORD: United Nations, Kashmir conflict, India, Pakistan, third party, conflict resolution, and right of self-determination.Â  IKHTISAR: Artikel ini berjudul âKeterlibatan Perserikatan Bangsa-Bangsa dalam Konflik Kashmirâ. Keterlibatan pihak ketiga atau mediasi merupakan salah satu metode untuk menyelesaikan konflik. Mediasi adalah proses penyelesaian konflik. Dalam konflik Kashmir, keterlibatan utama untuk resolusi konflik adalah peran PBB (Perserikatan Bangsa-Bangsa). Sebenarnya, Kashmir telah ditekan melalui proses sentralisasi dan sentralisasi yang berlebihan. Lagi pula, resolusi PBB memperkuat gerakan kemerdekaan Kashmir. Namun juga kenyataan bahwa, entah bagaimana dan dimana, PBB telah gagal dalam konflik Kashmir untuk memberikan sentuhan akhir untuk resolusinya. Selain itu, konflik Kashmir tetap menjadi sengketa lama dalam politik internasional. Keruwetan Kashmir bisa saja diselesaikan jika PBB telah mengambil tanggung jawabnya. Di sisi lain, kegagalan utama mediasi pihak ketiga dalam konteks Kashmir adalah penolakan yang kuat dari India untuk mediasi pihak ketiga. Maka tidak salah jika Kashmir menuntut bagian dan hak-hak mereka yakni hak penentuan nasib sendiri dan kemerdekaan. Semua pihak dalam konflik Kashmir harus menghormati perjanjian dan resolusi PBB dan melindungi jiwa manusia, yang tiada terkira. Akhirnya, dapat dikatakan bahwa India tidak bisa memenangkan hati rakyat Kashmir melalui kekuatan dan basis tentara, melainkan hanya mungkin melalui toleransi, cinta, menghormati martabat rakyat Kashmir, dan di atas semuanya melalui otonomi yang lebih besar.KATA KUNCI: Perserikatan Bangsa-Bangsa, konflik Kashmir, India, Pakistan, pihak ketiga, resolusi konflik, dan hak menentukan nasib sendiri.Â Â About the Authors: Dr. Hilal Ahmad Wani is a Research Fellow at Centre for Civilizational Dialogue UM (University of Malaya) in Kuala Lumpur, Malaysia; and Andi Suwirta, M.Hum. is a Senior Lecturer at the Department of History Education UPI (Indonesia University of Education) in Bandung, West Java, Indonesia. Corresponding authors are: wanihilal@gmail.com and atriwusidna@gmail.comHow to cite this article? Wani, Hilal Ahmad & Andi Suwirta. (2014). âUnited Nations Involvement in Kashmir Conflictâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.2(1), Maret, pp.41-50. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808, ISSN 2302-5808. Chronicle of the article: Accepted (January 5, 2014); Revised (February 5, 2014); and Published (Maret 24, 2014).